1997
DOI: 10.3109/00016359709115404
|View full text |Cite
|
Sign up to set email alerts
|

Oral Disease, Impairment, and Illness: Congruence Between Clinical and Questionnaire Findings

Abstract: In 1992 a questionnaire was sent to 50-year-olds in two Swedish counties. These self-report data were compared with clinical observations with regard to number of teeth, removable dentures, caries, and periodontitis. Complete information from both data sources was obtained for 1041 persons. The relevant questionnaire item explained 71% of the missing tooth variance. An agreement of 0.91 (Cohen's kappa) was obtained for removable dentures. A question about problems in opening the mouth differentiated clearly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
88
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 10 publications
14
88
2
1
Order By: Relevance
“…Regarding self-reported tooth loss, its validity has been shown using clinical examinations as the gold standard. 28 Any method for evaluating dietary intake is flawed in some way, and there is no gold standard for nutritional questionnaires; nevertheless, data for evaluating food consumption and nutritional intake in a population should be considered. 29 The lack of data related to sugar consumption in this study does not constitute a strong limitation, because the absolute intake of fat and sugar are strongly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding self-reported tooth loss, its validity has been shown using clinical examinations as the gold standard. 28 Any method for evaluating dietary intake is flawed in some way, and there is no gold standard for nutritional questionnaires; nevertheless, data for evaluating food consumption and nutritional intake in a population should be considered. 29 The lack of data related to sugar consumption in this study does not constitute a strong limitation, because the absolute intake of fat and sugar are strongly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…The implemented IEG, last dental visit, and Unmet dental need were statistically significant (in bold) a Adjusted for age, gender, education level, no flossing, frequency of toothbrush \twice a day, frequency of toothbrush change [2 months, last dental visit [1 year and unmet dental need hierarchical model contemplated factors from the contextual level as being mediators to the entire complex of individual determination. Self-reported health status is an alternative to clinical dental caries evaluation [6,7], and SRDC is considered valid for population-based health surveys [6,8]. In dentistry, self-reported knowledge is an economically reasonable opportunity for assessing oral health disorders in population-based multidisciplinary studies and reduces the necessity for time-consuming clinical examinations [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported health status is an alternative to clinical dental caries evaluation [6,7], and SRDC is considered valid for population-based health surveys [6,8]. In dentistry, self-reported knowledge is an economically reasonable opportunity for assessing oral health disorders in population-based multidisciplinary studies and reduces the necessity for time-consuming clinical examinations [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the association was further analyzed by creating two categories of remaining teeth (1-19 and 20-32 teeth), because these criteria for the number of teeth are widely used in research from several different age groups and in different countries (Axelsson & Helgadottir, 1995;Pitiphat et al, 2002;Ueno et al, 2010;Unell et al, 1997). Studies show that the number of natural teeth estimated by questionnaires is in good agreement with clinical examinations ( Pitiphat et al, 2002;Unell et al, 1997) and patients' reported number of remaining teeth provide reasonably valid data on the actual number of teeth within a population group (Ueno et al, 2010). Furthermore, self-reported data would be used for measuring oral health conditions in populations at lower cost, less resource involvement and within shorter timeframes (Jones et al, 2001).…”
Section: Discussionmentioning
confidence: 99%